Immunoproliferative Small Intestinal Disease: a Rare Disease with Common Presentation - Islam, M M Shahin Ul; Das, Nimai; Rahman, ATM Ataur (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Immunoproliferative Small Intestinal Disease is a rare type of lymphoproliferative disorder that affects the small intestine. We present a case of a 50-year-old female patient who was diagnosed with IPSID after presenting with chronic diarrhoea, abdominal pain and weight loss. The patient underwent endoscopy and biopsy, which has confirmed the presence of atypical lymphocytes in the small intestine. The patient was treated with chemotherapy and responded well to treatment. Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(2):131-134.